GAMBARAN PENGETAHUAN MASYARAKAT TENTANG KERACUNAN MAKANAN DI KELURAHAN HELVETIA TAHUN 2022 - Rusmauli Lumban Gaol; Sry Ayu Natalia Sihombing (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Food poisoning is a health problem causing severe illness and even death. Food poisoning caused by bacteria from food in Indonesia there are about 20 million cases of food poisoning per year. Around 600 million people worldwide fall ill after eating contaminated food, and 420,000 fatal cases occur every year. The most common disease caused by ingestion of contaminated food is diarrheal disease, which causes 550 million people to fall ill and 230,000 fatal cases every year. In Helvetia Medan there are 41 people who have had food poisoning and are undergoing treatment. treated at Medan Hospital after eating dinner at the hostel on Tuesday, February 8, 2017. The impact of food poisoning can cause several complications from mild to more serious. The most common complication is dehydration, while the more serious complication is hemolytic uremic syndrome. The method used in this research is descriptive method, with a total sampling technique of 48 people. The results show that the public's knowledge of food poisoning prevention is "good" 43 respondents (89.6%) and 5 respondents (10.4%) knowledgeable about food poisoning. It can be concluded that the Description of Public Knowledge About Food Poisoning at Jl.Beringin II Kelurahan Helvetia Medan 2022, has good knowledge. It is recommended to the public to maintain a clean and healthy lifestyle, especially in the provision and consumption of food and to add information related to how to prevent food poisoning.